2018
DOI: 10.1002/gch2.201700064
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Removal from Aqueous Solutions Using Poly(Styrene Sulfonate)/Nanoalumina Multilayer Thin Films

Abstract: In the present study, fluoride removal from drinking water is investigated using layer‐by‐layer (LbL) fabricated poly(sodium 4‐styrene‐sulfonate) (PSS)/Al 2 O 3 thin films. The surface morphology of the fabricated thin films is characterized using atomic force microscopy and field emission‐scanning electron microscopy. Optical profilometry is used to determine the self‐assembly of the multilayer thin films. The effect of various parameters such as adsorbent dosage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…(Johansson, Paul, Nys, & Roberts, ; Liu, Yang, Wen, & Liu, ; Senthilkumar, Vijayaraghavan, Thilakavathi, Iyer, & Velan, ). Furthermore, it is critically observed that the aluminum‐impregnated adsorbents such as nano‐alumina multilayer thin films, granular zirconium–aluminum, aluminum‐impregnated coconut fiber, and aluminum hydroxide‐coated activated carbon have reported higher sorption capacities that can be attributed to the improved interactions between fluoride and the sorbent surface charge activated by hydrogen bonding effects from the hydrogenated atmosphere (Amalraj & Pius, ; Naba Kumar, Bhaumik, & Datta, ; Prathna & Raichur, ; Wu, Chen, Ouyang, Lei, & Liu, ). However, studies on the removal of Al(III) using biochar are limited.…”
Section: Introductionmentioning
confidence: 99%
“…(Johansson, Paul, Nys, & Roberts, ; Liu, Yang, Wen, & Liu, ; Senthilkumar, Vijayaraghavan, Thilakavathi, Iyer, & Velan, ). Furthermore, it is critically observed that the aluminum‐impregnated adsorbents such as nano‐alumina multilayer thin films, granular zirconium–aluminum, aluminum‐impregnated coconut fiber, and aluminum hydroxide‐coated activated carbon have reported higher sorption capacities that can be attributed to the improved interactions between fluoride and the sorbent surface charge activated by hydrogen bonding effects from the hydrogenated atmosphere (Amalraj & Pius, ; Naba Kumar, Bhaumik, & Datta, ; Prathna & Raichur, ; Wu, Chen, Ouyang, Lei, & Liu, ). However, studies on the removal of Al(III) using biochar are limited.…”
Section: Introductionmentioning
confidence: 99%